Human Information Processing, Decision Style Theory and Accounting Information Systems: A Comment. - Tiessen, Peter; Baker, Dennis M. (The Accounting Review, 1977)
Abstract Comments on a study which used the decision style model of cognitive complexity to test whether complex integrative decision styles prefer more complex information input and use more information in decision making than cognitively low decision styles. Inconsistencies in the interpretations of results; Flaws in the empirical equivalents used.